1999
DOI: 10.1093/jnci/91.20.1725
|View full text |Cite
|
Sign up to set email alerts
|

Expression of K13/v-FLIP Gene of Human Herpesvirus 8 and Apoptosis in Kaposi's Sarcoma Spindle Cells

Abstract: These data suggest that functional v-FLIP is produced in vivo and that antiapoptotic mechanisms may be involved in the rapid growth of KS lesions, where only a few cells undergoing mitosis are generally observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
106
0
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(111 citation statements)
references
References 54 publications
4
106
0
1
Order By: Relevance
“…44,70 The tumorigenic interplay of these two viruses is mediated by the same ICs that have been shown to induce GBP-1 expression, and expression of all these cytokines has been demonstrated in KS tissue sections. 22,[37][38][39][40][41][42][43][44] In addition, in psoriasis and adverse drug reactions of the skin IFN-␥ expression has been detected.…”
Section: Discussionmentioning
confidence: 99%
“…44,70 The tumorigenic interplay of these two viruses is mediated by the same ICs that have been shown to induce GBP-1 expression, and expression of all these cytokines has been demonstrated in KS tissue sections. 22,[37][38][39][40][41][42][43][44] In addition, in psoriasis and adverse drug reactions of the skin IFN-␥ expression has been detected.…”
Section: Discussionmentioning
confidence: 99%
“…We subsequently showed that K13 protein also possesses the ability to activate the NF-kB pathway (Chaudhary et al, 1999b;Liu et al, 2002). As K13 is one of the few HHV-8-encoded proteins to be expressed in latently infected KS spindle cells (Sarid et al, 1998;Sturzl et al, 1999), in this report we have investigated its role in the upregulation of IL-8 expression and secretion and the signaling pathways involved in this process.…”
Section: Introductionmentioning
confidence: 95%
“…As discussed previously, KSHV ORFs 73, 72 and K13 are transcribed as a tricistron from the same promoter, P127880 in KSHV-infected cells. Since this tricistron has one 5′ ss, but two alternative 3′ ss (Figure 2), splicing of an intron of 499 nts from the tricistron leads to the selection of a 5′ ss proximal 3′ ss and results in production of the spliced tricistronic transcript (ORF73/72/K13) predominately responsible for LANA 1 translation [47,58,59]. However, the majority of the tricistrons splice over to the distal 3′ ss by removing a 4 kb intron, and consequently produce the bicistronic transcript (ORF72/K13) responsible for v-cyclin and v-FLIP translation.…”
Section: Mechanisms Possibly Involved In the Regulation Of Kshv Rna Smentioning
confidence: 99%